2013 Transducers &Amp; Eurosensors XXVII: The 17th International Conference on Solid-State Sensors, Actuators and Microsystems 2013
DOI: 10.1109/transducers.2013.6626939
|View full text |Cite
|
Sign up to set email alerts
|

Batch fabricated flexible tactile sensor based on carbon nanotube-polymer composites

Abstract: We developed a batch-processed, flexible tactile sensor using carbon nanotube (CNT)-polymer composites. The fabricated sensor consists of a flexible substrate (polyimide), four flexible sensing parts (CNT-polymer composites) and a bump structure (SU-8). CNT-polymer composite was patterned on polyimide substrate through large area screen printing process. The proposed sensor structure has advantages in high sensitivity, mechanical flexibility and facile fabrication process. It showed outstanding piezoresistive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Recently, Pyo et al [ 33 ] have proposed a flexible tactile sensor based on four CNT-PDMS sensing parts placed on a polyimide substrate with Cr/Au interdigitated electrodes and surmounted by a bump structure made of SU-8. In details, a 2% in weight of CNTs were dispersed into the PDMS copolymer by further addition of curing agent at a ratio 1:10 with respect to the CNT-PDMS mixture.…”
Section: Percolation Mechanismmentioning
confidence: 99%
“…Recently, Pyo et al [ 33 ] have proposed a flexible tactile sensor based on four CNT-PDMS sensing parts placed on a polyimide substrate with Cr/Au interdigitated electrodes and surmounted by a bump structure made of SU-8. In details, a 2% in weight of CNTs were dispersed into the PDMS copolymer by further addition of curing agent at a ratio 1:10 with respect to the CNT-PDMS mixture.…”
Section: Percolation Mechanismmentioning
confidence: 99%
“…CNT-PDMS composite was produced by the simple solvent evaporation method as shown in figure 3 [17]. It is difficult to disperse CNTs uniformly within the PDMS matrix if they are directly mixed, as individual CNTs tend to agglomerate together in a viscous fluid.…”
Section: Cnt-pdms Compositementioning
confidence: 99%
“…When approaching percolation threshold, MWNTs can not only improve the sensitive of piezoresistive composite much more than other allotropes but also decrease the influence on the impedance from ambient temperature [ 20 ]. A large amount of research has already been reported about the application of MWNTs/polymer composite in developing strain and force sensors in which the sensitive elements are fabricated in bulk size [ 6 , 21 , 22 ]; however, in this paper, a novel tactile sensor with the sensitive element in thin aligned fibers form is described. Thin fiber in sub-micrometer diameter not only constrains the dispersion of MWNTs and increases their alignment as well as electrospinning progress does [ 23 ], but also the drum collector arranges the polymer fibers parallel so that MWNTs in different fibers remain in the same orientation which makes SEs show anisotropy in electricity (see Section 4 ).…”
Section: Sensor Mechanism and Designmentioning
confidence: 99%
“…Among these mechanisms, the piezoresistive method is prevalent for its simple and low-cost preparation process with good flexibility [ 5 ]. Moreover, piezoresistive composite materials made up of the polymeric matrix and conductive fillers have been widely studied over the last decades because of their higher sensitivity and higher compatibility with complex curves than rigid materials such as microelectromechanical systems (MEMS) piezoresistors [ 6 , 7 , 8 ]. Although the composites are intrinsically sensitive and flexible, the bulky size (especially in the thick direction) of these materials would impede the full utilization of these good properties [ 9 ].…”
Section: Introductionmentioning
confidence: 99%